Short‐circuit current of a hydropower plant with consideration of constant switching and fault arc voltages - Darko Brankovic; Robert Schuerhuber (IET Generation, Transmission & Distribution)
Abstract The correct generator circuit breaker (GCB) dimensioning is essential for the safe and reliable operation of a power plant or generation system. The dimensioning is usually based on standardized calculation methods according to standards (IEC standard 60909‐0, IEC/IEEE standard 62271‐37‐013, IEEE Std C37), often supplemented by selected transient calculations. A non‐systematic approach can often be observed here, which does not adequately take into account significant influencing variables or operating states of the generator. This article therefore systematically examines various parameters that influence the short‐circuit current components of the generator and are relevant for the dimensioning of the generator circuit‐breaker: short‐circuit angle, operating point, impedance ratios, phase clearing, switching arc, and fault arc. The results of the current parameters most relevant to the dimensioning of the GCB were then compared for different calculation methods. Special attention was paid to the effect of the switching and fault arc, which were modelled as a constant arc voltage, and its effect on the short‐circuit currents is systematically recorded. This work aims to summarize all relevant variables that influence the generator short‐circuit current and are relevant for the dimensioning of the GCB and to present the different results based on a short‐circuit calculation according to the standard and transient calculation to create a basis for a proper dimensioning of the generator circuit breaker.